2021
DOI: 10.1002/ece3.8104
|View full text |Cite
|
Sign up to set email alerts
|

50,000 years of ice and seals: Impacts of the Last Glacial Maximum on Antarctic fur seals

Abstract: Icecan also influence populations indirectly through trophic links. For example, changes in sea ice algae can drive bottom-up ecosystem effects, while changes in the availability of sea ice as a hunting platform for organisms such as leopard seals and polar bears can result in top-down effects (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…Further comparisons with larger sample sizes and other measurements should be conducted in the future. However, the morphometric differences described here indicate an adaptation to colder conditions since population divergence (Cleary et al, 2021) and support the robust genetic evidence that SSI AFS are genetically distinct from those at SG.…”
Section: Inter-regional Body Size Comparisonsupporting
confidence: 81%
See 1 more Smart Citation
“…Further comparisons with larger sample sizes and other measurements should be conducted in the future. However, the morphometric differences described here indicate an adaptation to colder conditions since population divergence (Cleary et al, 2021) and support the robust genetic evidence that SSI AFS are genetically distinct from those at SG.…”
Section: Inter-regional Body Size Comparisonsupporting
confidence: 81%
“…However, recent genetic studies largely reject this hypothesis. Instead, a genetic break between eastern and western stocks, first postulated by Wynen et al (2000), was unequivocally confirmed by subsequent studies utilizing nuclear DNA markers (Humble et al, 2018;Cleary et al, 2019Cleary et al, , 2021 showing high levels of differentiation (Paijmans et al, 2020). Distinct clusters correspond to populations in the west and the east (Kerguelen, Heard, and Macquarie Islands; Humble et al, 2018;Paijmans et al, 2020).…”
Section: Antarctic Fur Seal Population Structurementioning
confidence: 93%
“…2018, Cole et al . 2019, Cleary et al . 2021), which can help to understand how species have responded to past major climatic and environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…2014) and marine species (Louis et al . 2020, Cleary et al . 2021), and this never been explored for Snowy Owls, an important species which structures the Arctic trophic network (Legagneux et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation